2016
DOI: 10.1158/1541-7786.mcr-16-0109
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 Deacetylates HMGN2 to Regulate Stat5a Activity and Breast Cancer Growth

Abstract: Stat5a is a transcription factor utilized by several cytokine/hormone receptor signaling pathways that promotes transcription of genes associated with proliferation, differentiation, and survival of cancer cells. However, there are currently no clinically approved therapies that directly target Stat5a, despite ample evidence that it contributes to breast cancer pathogenesis. Here, deacetylation of the Stat5a coactivator and chromatin remodeling protein HMGN2 on lysine residue K2 by HDAC6 promotes Stat5a-mediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…HMGN2 was also shown to promote breast cancer growth in response to prolactin. In this system, HMGN2 reduces the binding of linker histone H1 to chromatin regulatory regions, thereby enhancing STAT5 accessibility to promoter DNA, ultimately leading to increased proliferation of breast cancer cells [54,55]. Further analysis showed that the K2 residue of HMGN2 was deacetylated in primary breast tumors but highly acetylated in normal human breast tissue, implying that targeting HMGN2 deacetylation may be a viable treatment for this type of breast cancer [55].…”
Section: Cancermentioning
confidence: 99%
“…HMGN2 was also shown to promote breast cancer growth in response to prolactin. In this system, HMGN2 reduces the binding of linker histone H1 to chromatin regulatory regions, thereby enhancing STAT5 accessibility to promoter DNA, ultimately leading to increased proliferation of breast cancer cells [54,55]. Further analysis showed that the K2 residue of HMGN2 was deacetylated in primary breast tumors but highly acetylated in normal human breast tissue, implying that targeting HMGN2 deacetylation may be a viable treatment for this type of breast cancer [55].…”
Section: Cancermentioning
confidence: 99%
“…PRL-induced genes were previously identified by our laboratory through global RNA profiling (42,43), and the genes immediate early response 3 (IER3) and pleckstrin homologylike domain, family A, member 2 (PHLDA2) were chosen for further analysis based on their breast cancer relevance (see "Discussion"). PRL treatment resulted in increased expression of CISH, IER3, and PHLDA2 here (Fig.…”
Section: Prl Treatment Induces Chromatin Decompaction and Promotes Bimentioning
confidence: 99%
“…Most of the cell studies were performed to understand the function of a particular protein of interest. Excluding studies that link functional changes to KDAC activity on histones (and therefore exert a functional effect via gene regulation rather than a change in target acetylation status), these studies rely on one or more tools to manipulate either the level of KDAC expression or activity in the cell, and then measure the change in acetylation of the target protein, usually by immunoblotting using an acetylation specific antibody 31‐82 . (Note that we have only included studies that utilized human cells.…”
Section: Approaches For Kdac Substrate Identificationmentioning
confidence: 99%
“…First, many of these experiments have utilized KDAC inhibitors to reduce the amount of deacetylation, and then looked for changes in acetylation levels of putative substrate proteins 31‐39,83‐85 . While experimentally convenient, essentially all available inhibitors are capable of inhibiting multiple KDACs, due to the high degree of similarity between the KDAC active sites.…”
Section: Approaches For Kdac Substrate Identificationmentioning
confidence: 99%
See 1 more Smart Citation